Proteomic analysis of synovial fluid obtained from a dog diagnosed with idiopathic immune-mediated polyarthritis - Tan, Wei Miao; Lau, Seng Fong; Md Ajat, Mohd Mokrish; Mansor, Rozaihan; Megat Abd Rani, Puteri Azaziah; Rahmad, Norasfaliza (Elsevier, 2017)
This case study is to report the proteins detected by proteomic analysis of synovial fluid from a dog diagnosed with idiopathic immune-mediated polyarthritis, and to compare it with healthy dogs. Synovial fluid was collected via arthrocentesis from a dog diagnosed with immune-mediated polyarthritis. Protein precipitation was performed on the synovial fluid, followed by isoelectric focusing and 2-dimensional gel electrophoresis. The spots on the 2-dimensional gels were analyzed using MALDI-TOF/MS. The results were then analyzed against the MASCOT database. The results from the proteomic analysis revealed an abundance of several types of immunoglobulins together with the presence of complement C4b-binding protein alpha chain. Actin and keratin were also among the proteins detected. Proteomic studies, facilitate a better understanding of the different levels of proteins expressed during disease activity. Potential disease biomarkers can aid in the diagnosis of disease, as well as help in monitoring treatment efficacy and providing prognosis for the patient.